PENGENAAN PAJAK PERTAMBAHAN NILAI PADA ONLINE MARKETPLACE TOKOPEDIA - Aufa Yudhistira (Jurnalku, 2021)
Abstract The purpose of the study is to understand the e-commerce business model and process in the Tokopedia online marketplace and review the treatment of the imposition of Value Added Tax (VAT) on goods delivery transactions that occur in the Tokopedia online marketplace. The research method used is descriptive qualitative. The result of the research is that Tokopedia earns income from premium features used by merchants, not from purchasing activities made by buyers. Events when merchants use Tokopedia's premium features are events that are subject to VAT. An event when a merchant with PKP status delivers goods to the Buyer, VAT is payable. Invoice or payment details received by the buyer that are not listed have been subject to VAT on the purchase of goods. The buyer makes a payment to the escrow account which will then be forwarded to the merchant, so the escrow account is required to collect VAT from the buyer. Events when a merchant sends goods to a buyer using a courier service are events that are VAT payable. The invoice or payment details received by the buyer that are not listed have been subject to VAT for the use of goods delivery services via courier. Keywords : E-commerce, Tokopedia, Value Added Tax   Abstrak Tujuan penelitian adalah memahami model serta proses bisnis e-commerce pada online marketplace Tokopedia dan meninjau perlakuan pengenaan Pajak Pertambahan Nilai (PPN) atas transaksi penyerahan barang yang terjadi di online marketplace Tokopedia. Metode penelitian yang digunakan adalah kualitatif deskriptif. Hasil penelitian adalah Tokopedia mendapatkan penghasilan dari fitur premium yang digunakan oleh merchant, bukan dari kegiatan pembelian yang dilakukan oleh pembeli. Peristiwa saat merchant menggunakan fitur premium Tokopedia merupakan peristiwa yang terutang PPN. Peristiwa saat merchant yang berstatus PKP menyerahkan barang kepada Pembeli terutang PPN. Invoice atau rincian pembayaran yang diterima pembeli tidak tercantum telah dikenakan PPN atas pembelian barang. Pembeli melakukan pembayaran kepada escrow account yang selanjutnya akan diteruskan kepada merchant, sehingga escrow account wajib memungut PPN dari pembeli. Peristiwa saat merchant mengirimkan barang kepada pembeli menggunakan jasa kurir merupakan peristiwa yang terutang PPN. Invoice atau rincian pembayaran yang diterima pembeli tidak tercantum telah dikenakan PPN atas pemanfaatan jasa pengiriman barang melalui kurir. Kata kunci : E-commerce, Pajak pertambahan nilai, Tokopedia